INDEPENDENSI DAN KOMITMEN ORGANISASI: MEDIASI PENGARUH BRAINSTORMING DAN KEAHLIAN AUDITOR TERHADAP PENILAIAN RISIKO - Mulyono, Agus; Yazid, Helmi; Bastian, Elvin (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
This study analyzes the effect of brainstorming and auditor expertise on fraud risk assessment with auditor independence and organizational commitment as mediating variables. The research method uses a quantitative approach with a sample of 200 auditors from the Inspectorate General of the Ministry of Education and Culture. Data was collected through a questionnaire analyzed using the Structural Equation Modeling (SEM) method. The results of this study indicate that brainstorming has a positive effect on risk assessment, brainstorming has no effect on auditor independence, and brainstorming positively affects organizational commitment. Auditor expertise has a positive effect on risk assessment, auditor expertise does not affect organizational commitment, and auditor expertise positively affects auditor independence. Auditor independence has a positive effect on risk assessment, while organizational commitment does not affect risk assessment. The results of the mediation test show that auditor independence only has a mediating effect on the auditor's expertise in risk assessment.